Association between Circulating Fibroblast Growth Factor 21 and Aggressiveness in Thyroid Cancer - Kang, Yea Eun; Kim, Jung Tae; Lim, Mi Ae; Oh, Chan; Liu, Lihua; Jung, Seung-Nam; Won, Ho-Ryun; Lee, Kyungmin; Chang, Jae Won; Yi, Hyon-Seung; Kim, Hyun Jin; Ku, Bon Jeong; et al. (Cancers, 2019)
Fibroblast growth factor 21 (FGF21) plays important roles in regulating glucose, lipid, and energy metabolism; however, its effects in tumors remain poorly understood. To understand the role of FGF21 in regulating tumor aggressiveness in thyroid cancer, serum levels of FGF21 were measured in healthy subjects and patients with papillary thyroid cancer (PTC), and expression levels of FGF21, FGF receptors (FGFRs), and β-klotho (KLB) were investigated in human thyroid tissues. The cell viability, migrating cells, and invading cells were measured in PTC cells after treatment with recombinant FGF21. Higher serum levels of FGF21 were found in patients with thyroid cancer than in control participants, and were significantly associated with body mass index (BMI), fasting glucose levels, triglyceride levels, tumor stage, lymphovascular invasion, and recurrence. Serum FGF21 levels were positively correlated with the BMI in patients with PTC, and significantly associated with recurrence. Recombinant FGF21 led to tumor aggressiveness via activation of the FGFR signaling axis and epithelial-to-mesenchymal transition (EMT) signaling in PTC cells, and AZD4547, an FGFR tyrosine kinase inhibitor, attenuated the effects of FGF21. Hence, FGF21 may be a new biomarker for predicting tumor progression, and targeting FGFR may be a novel therapy for the treatment of obese patients with PTC.